Safety and efficacy of intensive blood pressure lowering after successful endovascular therapy in acute ischaemic stroke (BP-TARGET): a multicentre, open-label, randomised controlled trial. Issue 4 (April 2021) - Mazighi, Mikael; Richard, Sebastien; Lapergue, Bertrand; Sibon, Igor; Gory, Benjamin; Berge, Jerome; Consoli, Arturo; Labreuche, Julien; Olivot, Jean-Marc; Broderick, Joseph; Duhamel, Alain; Touze, Emmanuel; et al.
Summary: Background: High systolic blood pressure after successful endovascular therapy for acute ischaemic stroke is associated with increased risk of intraparenchymal haemorrhage. However, no randomised controlled trials are available to guide optimal management. We therefore aimed to assess whether an intensive systolic blood pressure target resulted in reduced rates of intraparenchymal haemorrhage compared with a standard systolic blood pressure target. Methods: We did a multicentre, open-label, randomised controlled trial at four academic hospital centres in France. Eligible individuals were adults (aged ≥18 years) with an acute ischaemic stroke due to a large-vessel occlusion that was successfully treated with endovascular therapy. Patients were randomly assigned (1:1) to either an intensive systolic blood pressure target group (100–129 mm Hg) or a standard care systolic blood pressure target group (130–185 mm Hg), by means of a central web-based procedure, stratified by centre and intravenous thrombolysis use before endovascular therapy. In both groups, the target systolic blood pressure had to be achieved within 1 h after randomisation and maintained for 24 h with intravenous blood pressure lowering treatments. The primary outcome was the rate of radiographic intraparenchymal haemorrhage at 24–36 h and the primary safety outcome was the occurrence of hypotension. Analyses were done on an intention-to-treat basis. BP-TARGET is registered with ClinicalTrials.gov, number NCT03160677, and the trial is closed at all participating sites. Findings: Between June 21, 2017, and Sept 27, 2019, 324 patients were enrolled in the four participating stroke centres: 162 patients were randomly assigned to the intensive target group and 162 to the standard target group. Four (2%) of 162 patients were excluded from the intensive target group and two (1%) of 162 from the standard target group for withdrawal of consent or legal reasons. The mean systolic blood pressure during the first 24 h after reperfusion was 128 mm Hg (SD 11) in the intensive target group and 138 mm Hg (17) in the standard target group. The primary outcome was observed in 65 (42%) of 154 patients in the intensive target group and 68 (43%) of 157 in the standard target group on brain CT within 24–36 h after reperfusion] (adjusted odds ratio 0·96, 95% CI 0·60–1·51; p=0·84). Hypotensive events were not significantly different between both groups and occurred in 12 (8%) of 158 patients in the intensive target and five (3%) of 160 in the standard target group. Mortality within the first week after randomisation occurred in 11 (7%) of 158 patients in the intensive target group and in seven (4%) of 160 in the standard target group. Interpretation: An intensive systolic blood pressure target of 100–129 mm Hg after successful endovascular therapy did not reduce radiographic intraparenchymal haemorrhage rates at 24–36 h as compared with a standard care systolic blood pressure target of 130–185 mm Hg. Notably, these results are applicable to patients with successful reperfusion and systolic blood pressures of more than 130 mm Hg at the end of procedure. Further studies are needed to understand the association between blood pressure and outcomes after reperfusion. Funding: French Health Ministry.